Analysis of Liquidity Ratios, Solvency Ratios and Profitability Ratios to Assess Financial Performance at PT Bank Jago Tbk for the Period 2020-2023 - Oktaviani, Hesti (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study was to determine the effect of liquidity ratios, solvency ratios, and profitability ratios on financial performance at a digital bank, namely PT Bank Jago Tbk during the 2020-2023 period. This research uses a quantitative approach with descriptive research methods. The data collection technique in this research is literature study. Where data is obtained from financial reports on the Indonesia Stock Exchange (IDX) and data from the official website of PT Bank Jago Tbk, namely www.jago.com. The value of the financial performance of PT Bank Jago Tbk during the 2020-2023 period as measured through liquidity, solvency, and profitability ratios has changed every year. Based on the calculation results of the liquidity ratio, it is considered to be in a fairly good position. Based on the calculation results of the solvency ratio, it is considered to be in a bad position. From the calculation of the profitability ratio of Return On Assets (ROA) and Return On Equity (ROE) it is known that the calculation results are below the average good assessment according to Bank Indonesia (BI). Based on the calculation results it is known that the percentage of BOPO obtained is below 94% based on the standard criteria set by Bank Indonesia. Based on the results of the Net Interest Margin (NIM) calculation, it can be seen that the bank is able to obtain a large net interest income and is above the average good assessment according to Bank Indonesia. Net interest income earned by banks through productive assets can be said to be quite high and banks are able to use their productive assets very well.